2018
DOI: 10.1038/s41467-018-05819-9
|View full text |Cite
|
Sign up to set email alerts
|

Peritectic titanium alloys for 3D printing

Abstract: Metal-based additive manufacturing (AM) permits layer-by-layer fabrication of near net-shaped metallic components with complex geometries not achievable using the design constraints of traditional manufacturing. Production savings of titanium-based components by AM are estimated up to 50% owing to the current exorbitant loss of material during machining. Nowadays, most of the titanium alloys for AM are based on conventional compositions still tailored to conventional manufacturing not considering the direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(77 citation statements)
references
References 43 publications
3
74
0
Order By: Relevance
“…LPBF materials are generally highly textured owing to the directional temperature gradient across the deposited layers that induce epitaxial growth along the building direction [27]. However, depending on the part usage, texture can be modified and reduced to some extent by changing scanning strategy [28] or modifying the alloy composition [29]. For the material investigated in the current study a difference in texture between contour region and bulk was observed.…”
Section: Resultsmentioning
confidence: 82%
“…LPBF materials are generally highly textured owing to the directional temperature gradient across the deposited layers that induce epitaxial growth along the building direction [27]. However, depending on the part usage, texture can be modified and reduced to some extent by changing scanning strategy [28] or modifying the alloy composition [29]. For the material investigated in the current study a difference in texture between contour region and bulk was observed.…”
Section: Resultsmentioning
confidence: 82%
“…Boron (B), [28,29] tungsten (W) [30] , and a number of rare-earth elements (La, Y, etc.) [31][32][33] have been shown to affect the phase transformation and produce a significant constitutional undercooling and an increase in the nuclei population to encourage equiaxed grain formation in Ti and Ti-based alloys. Nevertheless, although B has a large Q, its use as a grain refiner may be limited when its deleterious effect on ductility caused by the precipitation of titanium borides is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we mention in passing a tweak to the recovery approach to lower the dislocation density and hence the RX driving force: the substrate can be heated in situ along with the 3D‐printing (using electron beam, laser, or other heating resource) process. This in situ heating has shown its potential in one‐step manufacturing of newly designed/tailored Ti alloy and maraging steel,41,42 which does not require post‐manufacturing HT and thus is expected to be cheaper and faster, although its application for repairing damaged superalloy single crystals has not been reported. Preheating may also lower the temperature for recovery annealing and shorten its duration, depending on the preheating conditions.…”
mentioning
confidence: 99%